Role of 18F-FDG PET/CT in Erdheim–Chester Disease in the Era of Multimodality Imaging - Jois, Bhargavi; Ananthasivan, Rupa; Rawat, Parameswaran R. V. Sudarshan; Rakshit, Susmita (Indian Journal of Radiology and Imaging, 2021)
Erdheim–Chester disease is a rare disease with systemic non-Langerhans cell histiocytosis, the diagnosis of which with conventional imaging modalities is challenging. We describe a case of a 73-year-old woman who was referred with a progressive history of bilateral proptosis. The magnetic resonance imaging (MRI) orbit demonstrated bilateral orbital masses with optic nerve encasement. A subsequent 18F-FDG PET/CT scan showed multi-organ disease with involvement of the orbits, pericardium, aorta, pararenal fascia, and appendicular bones. Metabolically active, easily accessible areas were selected for CT-guided biopsy. The biopsy showed sheets of foamy histiocytes with the expression of CD 68 and CD 163 consistent with a diagnosis of Erdheim–Chester disease. The FDG PET/CT played a pivotal role in establishing the diagnosis with the assessment of disease extent and further guided in the targeted biopsy.
Keywords: Erdheim–Chester disease; FDG PET/CT; multimodality imaging